The Influence of Zakat on Economic Growth and Welfare Society in Indonesia - Elleriz Aisha Khasandy; Rudy Badrudin (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
Indonesia as a one of the most significant Muslim population in the world has developed zakat rapidly; it is shown by the development of the zakat regulation and establishes of Badan Amil Zakat Nasional (BAZNAS). Zakat has many benefit for economic both of macro and micro aspect, such as foster inclusive economic growth. The objective of this study are 1) to examine the influence of zakat on economic growth and welfare society which uses 3 (three) indicators i.e.HDI, Percentage of Poor People, and GINI Index and 2) to investigate whether items of Theory Planned Behavior influence of zakat payment. The researcher used Structural Equation Model (SEM) with PLS software. The result showed that zakat in Indonesia does not influence economic growth and welfare society. Besides that, welfare society Indonesia as a developing country has a negative value to HDI and GINI index but has a positive value to Percentage of Poor People.